Penentuan Pakan Rusa Bawean dengan Analisis Kotoran, di Pulau Bawean - Djuwantoko Djuwantoko; Danang Wahyu Purnomo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The research was conducted in the Bawean island, East Java, where endemic Bawean deer’s inhabited naturally. The objective was to assess what kind of plant species as food resources in natural habitat of Bawean deer. The most Bawean deer habitats particularly lowland forests, are under the greatest pressure. Logging and land conversion have caused dramatic decreases in the forest cover of Bawean island, mainly in lowland, and forest margins are progressively shifting towards higher elevations. In that conditions, therefore a management practices should be implemented soon, for improving deer habitat. This study was focused on availability of food resources in the natural habitat of Bawean deer. Using indirect methods in the field to assess the remaining of food resources, which was consumed by Bawean deer, and fecal analysis was executed for identifying food deer items. The result, there were many species of plants as a food resources including Imperata cylindrical (lalang), Pericampylus glaucus (ancucu), Caryota mitis (andudur), Discorea hispida (gadung), Symplocos adenophylla (kayu sape), Coelorhachis muricata (lampedung), Scheria hebecarpa (lanting-lantingan), Paspalum cunyugatum (lambu merah), Argyera mollis (rombok putih), Lygodium circinnatum (taliata), Nephrolepis hirsitula (rending-rendang), Tridax procumbens (kenci-kencian), Brachiaria distachya (kabak-kabakan alas), Frimbrisyllis dichotoma (lente-lentean). The availability of those food resources was affected by season i.e., dry and rainy season, and the feeding habit of Bawean deers can allow adapting to the habitat condition. Based on that figure the Bawean deers may have so many several of food items in their natural habitat.